Consumer remedies on the issue of halal under contract law - Naimat, Nasihah; Abu Bakar, Elistina; Muhammad Arif, Afida Mastura (Human Resource Management Academic Research Society, 2022)
Ubi jus, ibi remedium is a well-known Latin maxim which means that ‘where there is a right, there is a remedy’. This maxim asserts that in situations where the law has established a right, there should be a corresponding remedy for its breach. Therefore, in order to ensure that consumer rights are sufficiently protected by the law against unfair trade practices, remedy is the only means to ensure a consumer’s right to redress is protected. This article aims to analyse the extent to which contract law act as a redress mechanism for consumers on the issue of fake halal logo. The main questions to be answered are whether the contract law provides sufficient protection to consumers relating to fake halal logo. Whether the consumer who has consumed fake halal logo products and suffers no injury entitled to claim remedies under the contract law. The findings of this study showed that the remedies available under the contract law are not able to provide appropriate protection to the consumer on the issue of fake halal logo.